Risk factors and arterial hypertension - Rodrigues, Francisco (2019)
Cerebrovascular risk factors are increasingly present in modern society. These include a range of pathologies in which some of them are already beginning to be considered a serious public health problem. The study of these factors and the impact they may have on the morbomortality of the population should be a source of high concern for health authorities. The main objective was to understand the cerebrovascular and cardiovascular risk factors present in the study population and their relation with the presence of arterial hypertension. This cross-sectional, analytical and observational study was carried out in all municipalities in the district of Castelo Branco, in the interior region of Portugal. A total of 11316 individuals were studied, of which 55.6% belonged to the female gender (n = 6292) and 44.4% to the male (n = 5024). Of these 75.9% reported being sedentary, 63.5% were overweight and obese, 54.1% said they had a family history of hypertension and 41% had knowledge of having hypercholesterolemia. The results obtained demonstrate that there is a high prevalence of cerebrovascular and cardiovascular risk factors.